Improving the Quality of Transport Services of Urban Public Transport - Lopatynskyi, Yurii; Yekimov, Sergey; Nianko, Viktoriia; Pistunov, Ihor; Shevchenko, Valentyna (Transportation Research Procedia, 2022)
The modernization of urban transport requires new approaches not only in the organization of routes, but also the development of new forms of accounting for the number of transport services provided. Passengers expect from public transport to increase transport mobility, make trips more comfortable, and have routes that are convenient for them. To do this, it is necessary that it is also profitable for motor transport companies that serve the routes of urban public transport. The presence of low-demand and unprofitable urban public transport routes is not profitable for road transport enterprises and is an obstacle to their development.
XII International Conference on Transport Infrastructure: Territory Development and Sustainability
Keywords: Urban Public Transport; Transport Services; Quality of Transport Services; Transport; Improving the Quality of Transport Services